Ivan Vurnik's workers' colony - Medved, Ana (Studia Historica Slovenica, 2025)
The article examines political and architectural-historical questions of social housing in Maribor during the interwar years. Using an analysis of original plans and architectural tendencies from that time, different aspects and examples of social housing in Maribor and Slovenia are presented. Additionally, there are foreign influences, with the original projects from Vienna and other countries included in the wider theoretical context. With that theoretical base, architect Ivan Vurnik's work is represented in the context of a wider architectural question of social housing, and thus interweaves with then present political obstacles, found in the archival and newspaper sources of that time.
Keywords: architectural developments; architecturalhistory of 20th Century; architecture; arhitektura; arhitekturna zgodovina 20. stoletja; housing law; interwar era; Maribor; obdobje med obema vojnama; politicalcontext; politični kontekst; razvoj arhitekture; Rdeči Dunaj; Red Vienna; social housing; socialna gradnja; stanovanjski zakon; Vurnik, Ivan